Erratum: Effects of alloy disorder and confinement on phonon modes and Raman scattering in SixGe1-x nanocrystals: A microscopic modeling - Vasin, A. S. (2015)
Erratum: “Effects of alloy disorder and confinement on phonon modes and Raman scattering in SixGe1-x nanocrystals: A microscopic modeling” [J. Appl. Phys. 115, 143505 (2014)].